Boosting the turnover number of core–shell Al-ZSM-5@B-ZSM-5 zeolite for methanol to propylene reaction by modulating its gradient acid site distribution and low consumption diffusion. Issue 3 (9th January 2019) - Zhai, Yanliang; Zhang, Shaolong; Shang, Yunshan; Song, Yu; Wang, Wenxuan; Ma, Tong; Zhang, Luoming; Gong, Yanjun; Xu, Jun; Deng, Feng
Abstract : Hierarchical Al-ZSM-5@B-ZSM-5 core–shell zeolite was prepared to boost turnover number of MTP reaction. Abstract : Herein, a specific core–shell MFI zeolite was designed for the methanol to propylene (MTP) reaction. The core–shell structure of Al-ZSM-5@B-ZSM-5 and Al-ZSM-5@silicalite-1 were easily obtained via a two-step procedure, in which Al-ZSM-5 aggregate acted as the core and B-ZSM-5 or silicalite-1 as the shell. Their core–shell structures, acidity distribution and pore properties were characterized systemically, and new insights were gained into the synergetic effect of acid property and diffusion on the MTP reaction. The Al-ZSM-5@B-ZSM-5 zeolite exhibited a superior catalytic performance with a lifetime of 350 h (WHSV = 3 h −1 ), propylene selectivity of 49% and high turnover number of 4.3 × 10 6, while for the Al-ZSM-5 core, the corresponding values were 210 h, 43% and 5.2 × 10 5, respectively. Al-ZSM-5@silicalite-1 displayed the second best performance with the values of 250 h, 45% and 2.9 × 10 6, respectively. Gradient strong acid reduction from the core to the shell via the epitaxial growth of the silicalite-1 or B-ZSM-5 shell combined with an appropriate strong/weak acid ratio plays a vital role in inhibiting the hydrogen transfer reaction and thus gives a low consumption of propylene and low coke deposition. For the hydrogen transfer reaction of alkenes to form alkanes and aromatics, strong acid sites are required. Moreover, the acid sites originally existing on the external surface of the Al-ZSM-5 core were converted into internal acid sites due to the formation of an interface zone in the core–shell zeolite, possessing micropore characteristics, which in turn improve the shape selectivity and suppress coke deposition. Especially, the Al-ZSM-5@B-ZSM-5 zeolite displayed more weak acid sites and few strong acid sites on its shell surface, which are beneficial for the low formation of external coke and also account for the highest utilization of acid sites in the MTP reaction, high propylene selectivity and long lifetime.